Anusaba Composition: Reconstructing Bagarak Environmental Sounds into a Hybrid Soundscape - Nazir, Ahmad; Muchtar, Asril (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to reconstruct the environmental sound of bagarak as a cultural identity of Guguak Tinggi in a hybrid soundscape music composition. Bagarak is a profession that processes gold and silver raw materials into various jewelry with high aesthetic value. The artistic value of bagarak not only enriches art, but also flows the logic of art into people's thoughts, feelings, bodies and behavior in living life. Musically, bagarak plays an important role in the soundscape of Guguak Tinggi. Various sound elements from the community's social activities are present as a chain that continues to fill the flow of Guguak Tinggi's time and evolve with the times. This research uses ethnographic and historical methods. Data were obtained by diving into the lives of indigenous people sensitively and naturally, as well as through documentation. Data analysis was carried out qualitatively to understand the point of view of the culture owner, focusing on the identification of sound material and its meaning. The results show that the environmental sound of bagarak characterizes Guguak Tinggi, which has aesthetic value and reconstruction value.